REFERENCE SERUM VALUES OF UREA AND CREATININE IN CAPTIVE WHITE-LIPPED PECCARY (TAYASSU PECARI) IN A LIMA ZOO - Romero S., Mónica (2008)
The objective of this research was to establish reference serum values for urea and creatinine in the captive white-lipped peccary (Tayassu pecari). Serum samples from 44 adult animals (23 males and 21 females) from a captive colony in the Parque de las Leyendas Zoo (Lima, Peru) were collected after chemical inmobilization. Urea and creatinine were analyzed using colorimetric assays, and values were 27.4 ± 2.7 mg/dl and 2.8 ± 0.2 mg/dl respectively. No significant differences between sexes were found. Urea value was greater than those obtained in other studies probably due to the high protein content of the zoo diet.